Physico-chemical and nutritional attributes of cashew apple and its products - Suman K T (Department of Home Science, College of Horticulture, 2006)
The study on “Physico-chemical and nutritional attributes of cashew apple and its products” was undertaken to evaluate twenty six varieties of cashew apple maintained at Cashew Research Station, Madakkathara for various physico-chemical and nutritional attributes. Two products namely candy and tutty fruity were prepared from selected varieties and storage studies were carried out to find out changes in physico-chemical and nutritional attributes, organoleptic qualities and shelf life of products stored for a period of six months and the most suitable varieties for preparation of candy and tutty fruity were selected. With an objective of preparing candy and tutty fruity, analysis of cashew apples was carried out, which showed that the physico-chemical and nutritional attributes of cashew apple varied significantly among different varieties with an exception of insignificant variation in pulp weight. The highest and lowest fruit weight was noted in Priyanka and V-5 respectively. The variety Amrutha had the highest juice yield and juice residue ratio. The tannin content and other chemical and nutritional constituents have a direct impact on the quality of candy and tutty fruity. The variety Kanaka had the highest tannin content and lowest was in Amrutha and Anakkayam-1. Cashew apple was found to be low in acidity, pectin and reducing sugar. Eventhough the cashew apple is having a low content of protein and fat, it was found to be a rich source of carbohydrate, fibre, -carotene, vitamin C and minerals especially potassium. The highest vitamin C content of 367.26 mg 100 g-1 was noted in variety H-1610. The variety Madakkathara-2 had the highest phosphorus, manganese, sodium and potassium contents. The highest and lowest polyphenol oxidase activity was observed in V-1 and H-1593 respectively. After screening 26 varieties, 14 varieties were selected for the preparation of candy and tutty fruity and the quality attributes of the products were studied for a period of six months. The decreasing trend in acidity, tannin, pectin, ß carotene and vitamin C content of candy and tutty fruity may be due to low moisture content and practically nil microbial load. Due to biological inter conversion of natural products it was also observed that candy and tutty fruity showed increasing trend in the reducing sugar, total sugar, TSS and sugar acid ratio during storage. The percentage of mineral content of cashew apple candy and tutty fruity slightly increased on six months of storage due to the loss in moisture. In cashew apple candy and tutty fruity, overall acceptability decreased with increase in storage period. Browning and increase of sweetness showed a negative impact on acceptability which expressed a different flavour and taste in candy and tutty fruity stored for six months. Dharasree which had a low fibre and tannin content produced high quality candy and tutty fruity with an appealing golden yellow colour. Bacteria and yeast were not detected in candy and tutty fruity during six months of storage. Fungal count was observed in candy and tutty fruity through out the storage period, which increased with advancement of storage period. The increase in count was found to be minimum in both the products and the products had good shelf life. High sugar and low moisture content in candy and tutty fruity may not be favouring the microbial count. The most suitable varieties for the preparation of candy and tutty fruity were selected mainly based on crude fibre, tannin, sugar content and oragnoleptic scores. For the preparation of candy varieties viz. Amrutha, Anakkayam-1, Dharasree, V-5 and VTH 30/4 and for tutty fruity Amrutha, Anakkayam-1, Dharasree, H-1593 and V-5 were found to be most suitable. The cost for production of tutty fruity was higher than candy. From 1 kg cashew apple 745g candy was obtained whereas the yield of tutty fruity was only 715 g. Candy and tutty fruity can be prepared with low cost involvement from cashew apple and could provide a viable produc